Answer:
So, after solving the equation
we get value of x = -3
Explanation:
We need to find the value of variable x in the equation:
![(1)/(3)x-9=14x-7-13x](https://img.qammunity.org/2021/formulas/mathematics/high-school/45itr35jog7kd2gsmx5a91f0f8hxi57f9k.png)
Solving, the equation and to find the value of x
Combining like terms: (terms having x are like terms, other constants are like terms)
![(1)/(3)x-9=14x-7-13x \\(1)/(3)x-14x+13x=-7+9](https://img.qammunity.org/2021/formulas/mathematics/high-school/4q7cebq1t0kdv92g2k7cranhaw8u61sr9f.png)
Now taking LCM on left side:
![(1)/(3)x-14x+13x=-7+9 \\(1x*1-14x*3+13x*3)/(3)=2\\(1x-42x+39x)/(3)=2\\(-2x)/(3)=2](https://img.qammunity.org/2021/formulas/mathematics/high-school/bko7pecf8gvmpse4be2u6fhfo4ubgcbpm7.png)
Multiplying both sides by 3
![(-2x)/(3)*3=2*3\\-2x=6](https://img.qammunity.org/2021/formulas/mathematics/high-school/8w8ojxww6ogl9xfrmxvg4igxlt1lb7kd3p.png)
Dividing both sides by -2
![(-2x)/(-2)=(6)/(-2)\\x =-3](https://img.qammunity.org/2021/formulas/mathematics/high-school/vvupxw6n669rf50brk6y2uc1ifd53u8clb.png)
So, after solving the equation
we get value of x = -3